Quantum Mechanics - Zhang, Guo-Ping; George, Thomas F.; Si, Mingsu (De Gruyter Textbook, 2024)
This textbook provides ample opportunities for practice and real experimental demonstrations. Conceptual understanding and mastering key techniques are enhanced by rigorous derivations, numerous worked examples, more than 300 exercises, about 150 problems and 16 computer codes. The preface summarizes all of the key concepts and formulas, along with a detailed schedule for teaching. The first three chapters introduce the quantum idea, wave-particle duality, operators and measurement. The Noether theorem is invoked to introduce the Schrödinger equation, followed by applications to infinite and finite quantum wells, quantum tunneling, harmonic oscillators, Heisenberg equation of motion, uncertainty principle, blackbody radiation and photoelectric effect. Chapters 4 and 5 are on angular momentum, the hydrogen atom and time-independent approximate methods. Chapters 6 and 7 are on spin and time-dependent perturbation theory. Chapters 8, 9 and 10 are on molecular orbitals, energy bands, quantum transport, scanning tunneling microscopy, lattice vibrations, Berry phase and quantum computing. The book is intended for a one-semester or one-year course and is also appropriate for researchers in related fields.